2021
DOI: 10.1186/s12866-021-02120-6
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of continuous cropping of sweet potatoes on the bacterial community structure in rhizospheric soil

Abstract: Background Continuous cropping obstacles from sweet potatoes are widespread, which seriously reduce the yield and quality, causing certain economic losses. Bacteria of rhizospheric soil are the richest and are associated with obstacles to continuous cropping. However, few studies have examined how continuous sweet potato cropping affects the rhizospheric soil bacterial community structure. Results In the study, the Illumina MiSeq method was used to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 54 publications
5
30
1
Order By: Relevance
“…Most studies have reported that the differences in the relative abundance of Acidobacteria was attributable to soil pH differences; moreover, the relative abundance of Acidobacteria was significantly and negatively correlated with soil pH [68,69]. In the current study, Acidobacteria abundance was significantly and positively correlated with soil pH, which was consistent with the results of the research on sweet potato continuous cropping [70] and the study on diversity of bacterial community in cotton field [71]. This result may be related to the difference in response to soil environmental factors between different Acidobacteria subgroups or even between Acidobacteria in the same subgroup [68,72].…”
Section: Plos Onesupporting
confidence: 91%
“…Most studies have reported that the differences in the relative abundance of Acidobacteria was attributable to soil pH differences; moreover, the relative abundance of Acidobacteria was significantly and negatively correlated with soil pH [68,69]. In the current study, Acidobacteria abundance was significantly and positively correlated with soil pH, which was consistent with the results of the research on sweet potato continuous cropping [70] and the study on diversity of bacterial community in cotton field [71]. This result may be related to the difference in response to soil environmental factors between different Acidobacteria subgroups or even between Acidobacteria in the same subgroup [68,72].…”
Section: Plos Onesupporting
confidence: 91%
“…These fungal isolates exhibited the great ability to solubilize P, increase the growth of eggplant, and produce siderophores and indole acetic acid [6]. In addition, the use of organic residues as amendments exerts a great influence on soil microbial communities [45][46][47][48], which not only increases the soil organic matter level and long-term soil fertility, but also improves the soil health and productivity.…”
Section: Effects Of Different Organic/chemical Amendments In Rhizosph...mentioning
confidence: 99%
“…Tuber yield is closely related to soil quality, which is determined by a variety of factors including soil physical and chemical properties, enzyme activity, and microbial abundance [7][8][9]. However, with the single farming method, such as continuous planting, soil structure is destroyed, physical and chemical properties deteriorate, and storage capacity becomes poor, which in turn affects plant growth and development, leading to crop yield reduction [9][10][11][12]. As a result, new agricultural practices are urgently needed to address the worsening of soil quality and yield reduction.…”
Section: Introductionmentioning
confidence: 99%